Herbst Appliance palatally anchored in the treatment of dental class II malocclusion - Di Leonardo, Bruno; Contardo, Luca; Riatti, Riccardo (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
In this case report, Authors describe the correction of a class II malocclusion using only an Herbst appliance palatally anchored with miniscrews. Before sagittal correction in the same appliance we applied a palatal screw to obtain maxillary expansion. The device were removed after 12 months of treatment. The final result included the correction of Class II malocclusion by lower dentoalveolar compensation mainly. The lip function favorite the spontaneous correction of upper frontal torque with consequent improvement of facial esthetics. After a follow up of 12 months the clinical result is satisfactory in terms of occlusion and esthetics. This clinical case showed a simple orthopedic and dentoalveolar approach to correct transversal discrepancy, dental class II malocclusion and also frontal proclination only with one appliance in a very short treatment time.